(untitled) (Taqdir, 2025)
This study aims to explore the potential and opportunities for innovation that can be carried out by Madrasah Ibtidaiyah (MI) in facing the digital era. The research method used is library research and data collection through book reviews, documents, literature, notes, and journals. Data collection uses documentation techniques. The results of this study found that the main challenges in implementing educational innovation include gaps in access to technology, lack of teacher readiness, resistance to change, and educational policies that do not fully support. On the other hand, there are various great opportunities, such as the development of 21st century skills, personalized learning, integration of local wisdom, and multi-party collaboration through the pentahelix approach.